Manajemen Penyidikan Pidana, Potensi Implementasi Teknik Wawancara Investigasi Pada Kepolisian Indonesia - Adhikara, Rio; Anggoro Arrya, Satya Dhira; Sumirat, Jauhar Rizqullah (Civil Officium: Journal of Empirical Studies on Social Science, 2022)
Investigations are a major aspect of the criminal justice process. However, based on the reality on the ground, the investigations carried out by the police have not been able to produce a balancé between accurate investigation results and practices that continue to uphold human rights by applicable procedures and regulations. Therefore, it is necessary to adjust the investigation technique that is proportional and effective. This article identifies three interview/interrogation techniques that are potential to be practised, namely: third level, accusation approach, and information gathering approach. Existing police law regulations do not specify the details of investigative interview techniques in criminal cases. For this reason, it is necessary to have an official procedure that can be used as a reference in the investigation process. The review of interview techniques in this article is expected to be a separate view that motivates and contributes to improving the quality of investigative techniques by police investigators.